An Interpretive Structural Fuzzy Analysis for CPFR Implementation Barriers: A Food Supply Chain Case Study - Karadayi-Usta, Saliha (Springer International Publishing, 2019)
Collaborative planning, forecasting and replenishment (CPFR) reference model is a key guideline to manage a supply chain with a high level of coordination and integration. Although there are well-defined steps of CPFR model, the adoption of this reference model has many challenges at the implementation phase. In this study, the CPFR implementation barriers were discussed and reviewed with the supply chain experts of Metro Cash & Carry Turkey office, and a final list of these barriers were given a form. At the following part of the research methodology, the inter-relations of these barriers were determined with the same supply chain experts and an additional supply chain management academician by using a fuzzy scale. Sequentially, the relationships were examined with Fuzzy Interpretive Structural Modeling (FISM). Consequently, the interdependencies of the CPFR implementation barriers were extracted in order to identify the root causes of these barriers.